Case report: A rare case of very well-differentiated gastric adenocarcinoma of gastric type with a lymphovascular invasion - Chen, Jiaqi; Cui, Xiujie; Wu, Honglei; Zhou, Chengjun (Frontiers in Oncology, 2024)
Background Very well-differentiated gastric adenocarcinoma (VWDA) is a rare variant of gastric cancer, for which the diagnostic criteria and clinical behavior are not fully established. We reported a case of an intramucosal VWDA of gastric type with a lymphovascular invasion (LVI). Case presentation A 67-year-old female was diagnosed as intramucosal gastric adenocarcinoma after a biopsy at the local hospital 3 weeks ago and then visited our hospital for further treatment. The endoscopic examination in our hospital showed a rough, slightly faded, 30-mm, flat, and elevated lesion on the lesser curvature of the middle gastric body. Histopathologically, the lesion consisted of superficial foveolar-type papillary adenocarcinoma and deep pyloric gland-type tubular adenocarcinoma. The immunostaining results showed that the foveolar-type papillary adenocarcinoma was positive for MUC5AC and had a high index of Ki-67, but the pyloric gland-type tubular adenocarcinoma was positive for MUC6 and had a low index of Ki-67. Both components were negative for MSH2 and MSH6, which suggested the high microsatellite instability phenotype. Moreover, a LVI was detected in the lesion. The pathological diagnosis was VWDA of gastric type. Conclusion The case has unique histological and immunophenotypic characteristics, which not only indicates the importance of architectural features in the diagnosis of VWDA but also further proves that the aggressive behavior of VWDA is correlated with tumor histological type and immunophenotype.